PO232 Incidence and healthcare costs of viral meningitis in adults – a multicentre prospective observational study in england. (1st December 2017) - McGill, Fiona; Griffiths, Michael J; Bonnett, Laura; Martin, Antony; Geretti, Anna Maria; Michael, Benedict D; Beeching, Nicholas J; McKee, David; Adan, Guleed; Scarlett, Paula; Hart, Ian J; Mutton, Ken; et al.
Abstract : Background: As bacterial meningitis decreases in incidence, viral meningitis becomes relatively more important. The incidence and costs of viral meningitis in adults are unknown. Methods: An epidemiological study of adults with suspected meningitis in England, was carried out between 2011 and 2014. We estimated incidence and healthcare costs using patient level data from the Northwest of England, and extrapolated to estimate resource use throughout the UK. Results: Among 1117 patients enrolled, 638 (57%) had meningitis. 231/638 (36%) had viral meningitis, 99/638 (16%) bacterial and 267/638 (42%) unknown aetiology. Estimated annual incidences of viral and bacterial meningitis were 2.73 and 1.24 per 1 00 000 respectively. The yearly healthcare cost of viral and bacterial meningitis were similar: £3, 220, 343 (95% CI £1, 206, 963 – £4, 418, 424) and £4, 860, 218 (95% CI £3, 728, 598 – £6, 358, 419) respectively, p=0.57. The median length of stay for patients with viral meningitis was 4 days, increasing to 8 days in those treated with antivirals, which are of no proven benefit. Hospitalisation accounted for 79% of the cost. Conclusions: Viral meningitis is the predominant cause of meningitis in adults in the UK. The total annual healthcare costs could be reduced by earlier discharge. This might be achieved through speedier diagnostics and avoiding unnecessary treatments.